Dual loyalty and human rights: a bioethical analysis of the situation in South Africa - Ferlito, Brandon Allister (My University, 2019)
In a wide range of clinical situations, backgrounds, and roles, healthcare professionals are subjected to requests from governments (and in some instances from other powerful third parties) to relegate patient for the interests of third parties, generally those of the state. Despite several international and national ethics guidelines and human rights law instruments, many healthcare professionals still find themselves facing difficult dual loyalty conflicts, which violate ethics and human rights law. Dual loyalty conflicts can be described as simultaneous obligations, express or implied, to a patient and to a third party. Therefore, healthcare professionals, when confronted with a dual loyalty conflict, must be loyal to both their patients, as well as a third party. This loyalty is often not compatible between the interests of patients and a third party's interests. Dual loyalty conflicts thus continue to remain a challenge for HCPs, particularly in South Africa. Therefore, a new Bioethics and Human Rights Law framework is imperative, if HCPs are to avoid or manage dual loyalty conflicts in ethically and legally sound ways
A Dissertation Submitted to the Faculty of Health Sciences, University of the Witwatersrand (Wits), Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Medicine (MscMed) in Bioethics & Health Law, Steve Biko Centre for Bioethics August 2019